ChemInform Abstract: Cu2ZnSnS4 Thin Films Generated from a Single Solution Based Precursor: The Effect of Na and Sb Doping. Issue 41 (22nd September 2016) - Tiwari, Devendra; Koehler, Tristan; Lin, Xianzhong; Harniman, Robert; Griffiths, Ian; Wang, Lan; Cherns, David; Klenk, Reiner; Fermin, David J.
Abstract: Cu2 ZnSnS4 (CZTS) thin films are prepared by spin coating of a precursor solution on Mo‐coated glass substrates.